Forum of necessity in Quebec Private International Law: C.c.Q. art. 3136 - McEvoy, John (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 2005)
Article 3136 C.c.Q. is a departure from the general rules of jurisdiction applicable to a Quebec authority. Based on the principle of necessity and in the absence of an appropriate forum, it authorizes an authority to exercise jurisdiction in relation to a matter not subject to its direct jurisdiction when it is impossible or unreasonable for the parties to access a foreign authority and when the litigation has a sufficient connection with Quebec. Article 3136 thus confers a discretionary jurisdiction on a Quebec authority. This discretion is limited by the definitional elements expressed in article 3136 and has been further narrowed by an inappropriate interpretation by the Court of Appeal in Lamborghini. The critical factor is that necessity jurisdiction implies that the litigation is subject to an effective remedy in the Quebec forum. Availability of an effective remedy renders reasonable the exercise of necessity jurisdiction and the requirement that foreign litigation be instituted, unreasonable. However, the factor of remedy is ignored, or without expression, in both doctrine and jurisprudence. Supported by a comparative approach between the civil law and the common law, the first part presents a general analysis of this exceptional rule with particular attention to the Swiss law which inspired the drafters of article 3136. In the second part, article 3136 is considered in context with the general provisions of the Code and the legislative history of the provision is clarified. The third part analyzes the definitional elements of the article and the last part examines its application as reflected in the relevant jurisprudence.